Engaging Students in Bamboo Dancing: EFL Speaking Class in Senior High School - Maliqul Hafis (PT. Media Edukasi Borneo, 2020)
This study aimed to explore the implementation of Bamboo Dancing technique to engage the students in learning English as a foreign language (EFL) speaking. Classroom action research (CAR) was employed to the first-year students in one of State Senior High School Negeri in Kalimantan Barat. Observation, measurement, field notes were used to collect the data. From qualitative and quantitative data analyses, the data revealed that despite the difficulties that the teacher to control the class in the first cycle, this CAR was powerful to impact teaching practice in the second cycle. Furthermore, several positive changes in the mean score from 50, in the first cycle, and 76, in the second one. It is recommended that the results of this CAR pictured the attention of the importance of collaboration and cooperation between teacher and researcher to create meaningful teaching and learning through mutually respectful, supportive, and beneficial dialogue.